-12/7=-6w

Simple and best practice solution for -12/7=-6w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12/7=-6w equation:



-12/7=-6w
We move all terms to the left:
-12/7-(-6w)=0
We get rid of parentheses
6w-12/7=0
We multiply all the terms by the denominator
6w*7-12=0
Wy multiply elements
42w-12=0
We move all terms containing w to the left, all other terms to the right
42w=12
w=12/42
w=2/7

See similar equations:

| 5x-12x-24=-11 | | V=3.14(5a^2)8a+5 | | -4v/9=-12 | | 14d-12d=16 | | 9+2(6y-3)=-3(3y-7)+7y | | 3m+5=34 | | 2x+2=-x+17 | | u—14=29 | | 9x+12+9x+12=180 | | 3=3.95+.05x(10) | | X+7=3x+15 | | 2x+2x-52=124 | | 3=3.95x+.05(10) | | 17.93=3g+3.98 | | 4/5u=-20 | | -6n-20=-2n+491-3n) | | -20=4/5u | | -40=-8(8+c) | | 37.00=8g+3.96 | | 2|8+x|=2x-4 | | .0001x^2+.04x-1.6=0 | | 14+2x=20+1.50x | | 9a+6a=-60 | | 8=x/0 | | -9=3v-2v | | 35t+25=40t | | 8-2y=9 | | 2².3¹.4ⁿ.5³.0²+x²=25 | | -2x=0.375 | | 9(c-4)=36 | | 4/3z=20. | | 9(4x+8)=120 |

Equations solver categories